PENANGGULANGAN BENCANA BANJIR DI SUNGAI BATANG MERAO PADA BADAN PENANGGULANGAN BENCANA DAERAH KOTA SUNGAI PENUH: NANIK MANDASARI, S.IP, M.Si - NANIK MANDASARI, S.IP., M.Si (LPPM STIA Nusantara Sakti, 2020)
Analysis of Flood Disaster Management in Batang Merao River at Sungai Penuh Regional Disaster Management Agency. Flooding is an event where land which is usually dry (not swampy areas) becomes inundated by water, this is caused by high rainfall and topographic conditions in the form of lowlands to sunken areas. In addition, the occurrence of flooding can also be caused by runoff which overflows and its volume exceeds the drainage capacity of the drainage system or river flow system. The occurrence of flood disasters is also caused by the low ability of soil infiltration, so that the soil is no longer able to absorb water. Flooding can occur due to rising water levels due to rainfall above normal, changes in temperature, embankments / dams that break, fast melting snow, obstructed water flow in other places. The purpose of this research is to find out how the Flood Disaster Management in Batang Merao River in Sungai Penuh City Regional Disaster Management Agency. This study uses a qualitative approach that examines an object of research by studying in its entirety and in depth rather than looking at the relationship of two or more variables, where the results of the study will be processed based on the interpretive researcher and described in a descriptive form. Data obtained through field interviews with 7 informants namely 1 key informant and 6 ordinary informants. Flood mitigation consists of prevention and mitigation, preparedness, emergency response and rehabilitation and reconstruction. Based on the existing work program, all activities have been carried out by the Sungai Penuh City Regional Disaster Management Agency in flood mitigation in Sungai Merao River Sungai Penuh which is guided by Law Number 24 Year 2007.